Pre‐heart failure at 2D‐ and 3D‐speckle tracking echocardiography: A comprehensive review. Issue 2 (13th January 2022) - Singh, Ram B.; Sozzi, Fabiola B.; Fedacko, Jan; Hristova, Krasimira; Fatima, Ghizal; Pella, Daniel; Cornelissen, Germaine; Isaza, Adrian; Pella, Dominik; Singh, Jaipaul; Carugo, Stefano; Nanda, Navin C.; et al.
Abstract: Chronic heart failure (CHF) has different stages and includes pre‐HF (PHF), a state of high risk of developing myocardial dysfunction and advanced CHF. Some major behavioral risk factors of PHF might predispose to biological risk factors such as obesity, diabetes mellitus, dyslipidemia, hypertension, myocardial infarction, and cardiomyopathy. These risk factors damage the myocytes leading to fibrosis, apoptosis, cardiac hypertrophy, along with alterations in cardiomyocyte' size and shape. A condition of physiological subcellular remodeling resulting into a pathological state might be developed, conducting to PHF. Both PHF and heart failure (HF) are associated with the activation of phospholipases and protease, mitochondrial dysfunction, oxidative stress and development of intra‐cellular free Ca 2+  [Ca 2+ ]i overloading to an elevation in diastolic [Ca 2+ ]i . Simultaneously, cardiac gene expression is activated leading to further molecular, structural and biochemical changes of the myocardium. The sub‐cellular remodeling may be intimately involved in the transition of cardiac hypertrophy to heart failure. 2D‐ and 3D‐speckle tracking echocardiography (STE) have been used to quantify regional alterations of longitudinal strain and area strain, through their polar projection, which permits a further assessment of both sites and degrees of myocardial damage. The examination of strain can identify sub‐clinical cardiac dysfunction or cardiomyocyte remodeling. During remodeling of the myocardium cardiac strain is attenuated, therefore it is an indicator of disease assessment.